Design of Blind Assistance System Using Refreshable Braille Display - Atish Peshattiwar; Sandeep Kakde; Kuldeep Pande; Vilas alagdeve; Abhinav Parkhi (Journal of Electronic Design Engineering, 2018)
In this paper, we demonstrate that Braille embosser is a type of device which is very useful for the initial stage Braille language learner. Here the input is provided with the help of serial port by mobile through Bluetooth module. This input is in the form of alphabetical form so the input is converted into Braille language which is displayed with the help of actuators. Blind assistance system also allows visually impaired people to do common tasks such as reading in Braille and reading documents. It is a portable device, they can carry wherever they want so that they could get information of place they are visiting with ease. As this device detect the obstacles and also determine at what distance obstacle is person can safely use this device for indoor purpose.